2011
DOI: 10.1183/09031936.00111410
|View full text |Cite
|
Sign up to set email alerts
|

Elemental carbon exposure and lung function in schoolchildren from Mexico City

Abstract: Though exposure to air pollution has a detrimental effect on respiratory health, few studies have examined the association between elemental carbon exposure and lung function among schoolchildren. The aim of the present study was to present the association between short-term elemental carbon exposure and lung function in schoolchildren from Mexico City.55 asthmatic and 40 non-asthmatic children were followed for an average of 22 weeks. A spirometry test was performed every 15 days during follow-up. Portable ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…For example, exposure to PM 2.5 or PM 10 can decrease lung function and increase blood pressure and heart rate in the cardiovascular and respiratory system [33], [53][55]. Exposure to volatile organic compounds was associated with the levels of IL-6 and TNF-α in the immune system [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposure to PM 2.5 or PM 10 can decrease lung function and increase blood pressure and heart rate in the cardiovascular and respiratory system [33], [53][55]. Exposure to volatile organic compounds was associated with the levels of IL-6 and TNF-α in the immune system [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…This focus overlooked a comparably long, if less ramified, history of filter optics studies using PTFE membranes as the collection substrate (Szkarlat and Japar 1981;Bennett and Patty, 1982;Campbell et al 1989Campbell et al , 1995Clarke et al 1996;Huffman 1996;Chow et al 2000;Taha et al 2007). Optical transmittance measurements are sometimes added to PTFE measurement suites as a proxy determination for "black carbon" (Cahill et al 1984;Nejedly et al 2003;Cuccia et al 2010;Barraza-Villarreal et al 2011) and, with sufficient spectral resolution, environmental tobacco smoke (Lawless et al 2004;Yan et al 2011). Massabo et al (2013) recently developed a multi-wavelength and multiangle optical system to make off-line MAAP-like absorption measurements on PTFE as well as quartz fiber filters.…”
Section: Ptfe Filters and The Improve Networkmentioning
confidence: 99%
“…de Medeiros et al (2009) conducted a case–control study in 14 districts of São Paulo that showed that infants born to women in regions with the highest levels of traffic-related pollution (upper quintile) had an almost 50% increased risk of early neonatal death compared with those living in areas with the lowest pollution [adjusted odds ratio (OR) = 1.47; 95% confidence interval (CI): 0.67, 3.19]. Exposure to traffic-related pollution in Latin America has been associated with increased otitis media (Brauer et al 2006), increased asthma, more severe asthma symptoms, and lower lung function (Barraza-Villarreal et al 2011; Romieu et al 2008; Wichmann et al 2009). …”
Section: Specific Environmental Health Threats To Children In Latin Amentioning
confidence: 99%